Distinct C9orf72-Associated Dipeptide Repeat Structures Correlate with Neuronal Toxicity. - Brittany N Flores; Mark E Dulchavsky; Amy Krans; Michael R Sawaya; Henry L Paulson; Peter K Todd; Sami J Barmada; Magdalena I Ivanova (PLoS ONE, 2016)
Hexanucleotide repeat expansions in C9orf72 are the most common inherited cause of amyotrophic lateral sclerosis (ALS) and frontotemporal dementia (FTD). The expansions elicit toxicity in part through repeat-associated non-AUG (RAN) translation of the intronic (GGGGCC)n sequence into dipeptide repeat-containing proteins (DPRs). Little is known, however, about the structural characteristics and aggregation propensities of the dipeptide units comprising DPRs. To address this question, we synthesized dipeptide units corresponding to the three sense-strand RAN translation products, analyzed their structures by circular dichroism, electron microscopy and dye binding assays, and assessed their relative toxicity when applied to primary cortical neurons. Short, glycine-arginine (GR)3 dipeptides formed spherical aggregates and selectively reduced neuronal survival compared to glycine-alanine (GA)3 and glycine-proline (GP)3 dipeptides. Doubling peptide length had little effect on the structure of GR or GP peptides, but (GA)6 peptides formed β-sheet rich aggregates that bound thioflavin T and Congo red yet lacked the typical fibrillar morphology of amyloids. Aging of (GA)6 dipeptides increased their β-sheet content and enhanced their toxicity when applied to neurons. We also observed that the relative toxicity of each tested dipeptide was proportional to peptide internalization. Our results demonstrate that different C9orf72-related dipeptides exhibit distinct structural properties that correlate with their relative toxicity.